2019
DOI: 10.21815/jde.019.088
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Interprofessional Pediatric Oral Health Clerkship on Advancing Interprofessional Education Outcomes

Abstract: The aim of this study was to evaluate the effectiveness of an innovative pediatric interprofessional education clinical experience using oral‐systemic health as the clinical population example for improving the self‐reported interprofessional competencies of family nurse practitioner, dental, and medical students. The objectives of the interprofessional experience were for students to apply pediatric oral health assessment, identify the pediatric oral‐systemic connection, and practice a team‐based approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…7 Additionally, ICCAS is now being used to assess competence after being immersed in interprofessional practice-based settings as well. 12 The retrospective pre-post design can present with bias associated with social desirability, effort justification, and cognitive dissonance, which may have impacted the results. Moreover, the varying levels of education of students from the other professional schools could have also influenced the accuracy of the results.…”
Section: Discussionmentioning
confidence: 99%
“…7 Additionally, ICCAS is now being used to assess competence after being immersed in interprofessional practice-based settings as well. 12 The retrospective pre-post design can present with bias associated with social desirability, effort justification, and cognitive dissonance, which may have impacted the results. Moreover, the varying levels of education of students from the other professional schools could have also influenced the accuracy of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to 2016, there were very few IPE studies that included dental students; that has changed as accreditation requirements have increased both the interest and expansion of IPE 12 . Recent literature includes a more representative sample of IPE student initiatives comprised of dental, medical, and family nurse practitioner students 13 ; dental, medical, nursing, and pharmacy students 14 ; dental and medical students 12 ; nurse practitioner and dental students 15 ; nursing, medical, dental, pharmacy, optometry, occupational therapy, physical therapy, and social work students 9 ; and nursing and dental hygiene students 16 …”
Section: Introductionmentioning
confidence: 99%
“…Reports of IPE experiences were either didactic, 17–19 clinical, 12,13,15,16 a combination of didactic and clinical, 14 simulation, 20,21 or workshops 9 . Studies used measurement strategies that ranged from pre‐post surveys using the Readiness for Interprofessional Learning Scales (RIPLS), 12,17 the Interprofessional Collaborative Competency Attainment Survey (ICCAS), 9,16,19–21 to semi‐structured interviews 8,22,23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Some studies have reported that health professions students had improved ICCAS scores from pretest to posttest following their IPE experience, which suggested an effective IPE strategy could help students develop interprofessional competence. [11][12][13][14] In these teaching activities, it is very important to engage students in IPE and influence their attitudes towards this method because negative attitudes can hinder learning via IPE. 6 Tools such as the Readiness for Interprofessional Learning Scale (RIPLS) 15 and the extended version, 16 the Interdisciplinary Education Perception Scale (IEPS), 17 have been used to evaluate attitudes about interprofessionalism.…”
mentioning
confidence: 99%